안와에 발생한 Langerhans 세포 조직구증 - 신정철; Jung Chul Shin (Daihan angwa haghoi jabji, 1996)
Langerhans 세포 조직구증은 주로 어린이에서 볼수 있는 원인 미상의 드문 질환으로 몸안의 여러 조직에 조직구의 비정상적인 증식과 침윤을 특징으로 하는 질환이다. 이에 저자는 우안 상안검의 종괴를 주소로 내원한 4세 남아에서 안와를 침범한 Langerhans 세포조직구증을 경험하였기에 보고하는 바이다. 상기 환자는 방사선학적 검사상 우측전두골의 골융해성병변을 보이는 연부조직의 종괴와 광학및 전자 현미경검사상 테니스 라켓 모양의 Birbeck 과립을 함유한 Langerhans 세포가 관찰되어 Langerhans 세포 조직구증으로 확진되었으며 그후 방사선 치료를 시행하였고 조사 후 4년간 추적조사 결과 현재까지 재발의 소견은 보이지 않고 있다(한안지 37:1946~1950, 1996). Langerhans` cell histiocytosis is a rare childhood disease of unknown etiology that is characterized by abnormal proliferation and infiltration of histiocytic cells in various tissues. The authors experienced a case of Langerhans` cell histiocytosis in 4-year-old man who had swelling of the right upper eyelid. Radiologic examination demonstrates a osteolytic soft tissue mass in the right orbit. The light microscopic and electromicroscopic examinations demonstrates a number of histiocytes containing its cytoplasmic racket-shaped Birbeck granule. Then, we confirmed the Langerhans` cell histiocytosis in the right orbit and the raditherapy was performed. No recurrence occured more than four years after the initial radiotherapy(J Korean Ophthalmol Soc 37:1946~1950, 1996).